1997
DOI: 10.1097/00005537-199708000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hypopharyngeal Cancer Patient Care Evaluation

Abstract: A survey was conducted to identify demographics and standards of care for treatment of hypopharyngeal squamous cell carcinoma in the United States. Data were accrued from voluntary submission of cancer registry and medical chart information from 769 hospitals representing 2939 cases diagnosed from 1980 to 1985 and 1990 to 1992. Clinical findings, diagnostic procedures employed, treatment practices, and outcome are presented. Overall, 5-year disease-specific survival was 33.4%, which segregated to 63.1% (stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
148
3
11

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(173 citation statements)
references
References 28 publications
11
148
3
11
Order By: Relevance
“…The socio-demographic characteristic of the studied population is generally consistent with previously published data from developing countries [2]. Vast majority (83%) presented with loco-regionally advanced disease concordant with the natural history of hypopharyngeal cancers where extensive submucosal invasion and lymphatic spread is common [3,4]. The estimated loco-regional control of 47.8% and 34.7% and disease-free survival of 43.8% and 28.8% in the non-surgical management of advanced hypopharyngeal cancer (stage III and IV respectively) at 3-years compares favorably to similar large cohorts reported in the indexed medical literature [13Á16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The socio-demographic characteristic of the studied population is generally consistent with previously published data from developing countries [2]. Vast majority (83%) presented with loco-regionally advanced disease concordant with the natural history of hypopharyngeal cancers where extensive submucosal invasion and lymphatic spread is common [3,4]. The estimated loco-regional control of 47.8% and 34.7% and disease-free survival of 43.8% and 28.8% in the non-surgical management of advanced hypopharyngeal cancer (stage III and IV respectively) at 3-years compares favorably to similar large cohorts reported in the indexed medical literature [13Á16].…”
Section: Discussionsupporting
confidence: 88%
“…In developing countries, including India, hypopharyngeal cancers are relatively more common constituting 20Á35% of all HNSCC [2]. Hypopharyngeal cancers are characterized by advanced disease at presentation with extensive submucosal spread, high risk of regional lymphatic involvement and relatively high propensity of distant metastases [3,4]. The current treatment paradigms for hypopharyngeal cancers aim to maximize loco-regional control while attempting to preserve laryngeal and pharyngeal form and function, whenever possible.…”
mentioning
confidence: 99%
“…The standard treatment of advanced hypopharyngeal cancer is surgery and postoperative radiotherapy (Vandenbrouck et al 1977;Pingree et al 1987;Frank et al 1994;Axon et al 1997;Hoffman et al 1997;Eckel et al 2001), while chemoradiotherapy aimed at larynx-preservation has recently been reported (Kraus et al 1994;Clayman et al 1995;Lefebvre et al 1996;Zelefsky et al 1996;Samant et al 1999). Not all patients with hypopharyngeal cancer are treated by surgery for various reasons such as unresectable primary cancer or lymph node metastasis, patient refusal, and severe cardiopulmonary disorder (Eckel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hpc have high rates of tobacco-and alcohol-related comorbidities and second cancers and frequently come from lower socioeconomic backgrounds 3,4 . Late presentation is typical, with approximately 70%-90% of patients having stage iii or iv disease at the time of presentation, and is at least in part attributable to the anatomy and location of the hypopharynx [3][4][5][6] . The underlying disease-related biologic factors are less well understood, but compared with other head-and-neck sites, hpcs have high rates of multicentricity, submucosal spread, and regional and distant metastasis 7 .…”
mentioning
confidence: 99%
“…The underlying disease-related biologic factors are less well understood, but compared with other head-and-neck sites, hpcs have high rates of multicentricity, submucosal spread, and regional and distant metastasis 7 . In retrospective series, approximately 60% of patients treated with curative intent experience disease relapse or residual disease, and up to 50% of recurrences involve distant failure 3,4 .…”
mentioning
confidence: 99%